Phosphorus availability and solar radiation efficiency in carrot (Daucus carota L.) cultivation in volcanic soils. (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
The adoption of more efficient management practices, such asrecognizing the adequate level of P availability (Olsen) in the soil, canresult in improved production efficiency in the carrot (Daucus carota L.)cropping system. Complementarily, knowing the behavior of radiationuse efficiency (EUR) is relevant in the optimization of resources (Pfertilizer and radiation), due to the continuous concern forenvironmental impact and for the reduction of production costs. Theobjective of this work was to evaluate the EUR performance of twocommercial carrot cultivars, across five levels of P-Olsen availability,under field conditions (13, 16, 19, 24, 28 ppm). The experiment wasestablished at the Santa Rosa Experimental Station (39º47'S; 73º14'W),belonging to the Universidad Austral de Chile (UACh) located in the cityof Valdivia in the Los Ríos Region, during the 2010-2011 growing season.EUR (g DM MJ-1) was calculated using photosynthetically active radiation(RIFA) and biomass (aerial and total). In this study, EUR of D. carotacultivars was not influenced by soil P-Olsen availability (p>0.05), butdifferences (p